Effect of flooding on growth and yield of mungbean genotypes (Bangladesh Journal of Agricultural Research, 2016)
The field experiment was carried out with some selected mungbean genotypes viz. IPSA-13, VC-6173A, BU mug 2, BARI Mung-5 and IPSA-12 to observe the effect of 4-days flooding on their growth and yield of mungbean under field conditions at Bangabandhu Sheikh Mujibur Rahman Agricultural University, Gazipur, Bangladesh during September to November, 2011 maintaining 3-5 cm standing water at 24 days after emergence. Days to flowering and maturity delayed in flooded plants over control depending on the genotypes. Flooding significantly reduced Total Day Matters (TDM), number of pods per plant, seed size and seed yield of the mungbean genotypes over control. Considering higher seed yield, larger seed size and less yield reduction relative to control VC-6173A, BU mug 2 and IPSA-13 were found tolerant to soil flooding condition.Bangladesh J. Agril. Res. 41(1): 151-162, March 2016